The effect of bilingualism on the brain is modulated by language experience. (31st December 2021) - Calabria, Marco; Voits, Toms; Rothman, Jason; Robson, Holly; Marín, Lidón Marín; Costumero, Víctor; Aguirre, Naiara; Pliatsikas, Christos
Abstract: Background: Research has shown that lifelong bilingualism may contribute to cognitive reserve in neurodegenerative diseases as shown by a delay of the age at symptom onset in bilinguals with different types of dementia. However, the study of the neural mechanisms behind this bilingual advantage is limited, especially for the preclinical stages of dementia, such as Mild Cognitive Impairment (MCI). Additionally, most of the studies have operationalised bilingualism as a dichotomous variable, despite the fact that language experience results from a combination of different factors (language usage, frequency of language switching, age of second language acquisition, and language proficiency). Method: In the present study we investigated cortical and subcortical grey matter structure volume, and episodic memory performance, in a group of bilingual individuals with MCI by considering their linguistic profile. Specifically, we compared active bilingual speakers of Spanish and Catalan and bilinguals who have good knowledge of their second language but without any active usage of it. This classification is based on the results of a previous study in which we found that actively speaking the two languages promotes the delay of symptoms in individuals with MCI. Result: The results reveal that active bilingualism significantly delays the onset of MCI symptoms. Additionally, active bilingualism is also shown to result in increased cortical grey matter in the right supramarginal gyrus, increased bilateral hippocampal volume and reshaping of the right amygdala and right caudate nucleus. Conclusion: These results are compatible with the hypothesis that bilingualism protects against cognitive decline via neural compensation mechanisms and by increasing neural efficiency in individuals with MCI.